1989
DOI: 10.1111/j.1471-0528.1989.tb03327.x
|View full text |Cite
|
Sign up to set email alerts
|

Preterm labour in twin pregnancies: can it be prevented by hospital admission?

Abstract: Summary. Women attending a twin pregnancy antenatal clinic underwent cervical palpation to calculate a cervical score by subtracting dilatation from length. Those with a score of −2 or less at or before 34 weeks are at especially high risk of preterm labour. A total of 139 such women were randomly allocated either to receive bed‐rest in hospital or to continue conventional outpatient management. No beneficial effect of bed‐rest could be identified in prolonging twin pregnancy or improving fetal outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 7 publications
0
26
0
Order By: Relevance
“…A Cochrane review evaluating inpatient management with bed rest in twins did not demonstrate any difference with regard to the risk of preterm delivery 23 . Only one study evaluated subjects with evidence of cervical change and it also did not demonstrate a significant difference in outcomes, including preterm delivery 24 . No trials evaluating activity restrictions or prophylactic tocolysis in twin pregnancies with a shortened cervix were identified.…”
Section: Discussionmentioning
confidence: 99%
“…A Cochrane review evaluating inpatient management with bed rest in twins did not demonstrate any difference with regard to the risk of preterm delivery 23 . Only one study evaluated subjects with evidence of cervical change and it also did not demonstrate a significant difference in outcomes, including preterm delivery 24 . No trials evaluating activity restrictions or prophylactic tocolysis in twin pregnancies with a shortened cervix were identified.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that prophylactic leave of absence from work did not improve the outcome of a twin pregnancy. Crowther et al ( 1989 ) and MacLennan et al ( 1990 ) also found that bed rest had no bene fi cial outcome in twin survivals. Indeed, "…evidence is accumulating that rest may even increase premature labour" (Thornton and Rout 1990 ; see also Andrews et al 1991 ) .…”
Section: Morbidity and Mortalitymentioning
confidence: 89%
“…In twin pregnancies with cervical dilatation, bed rest in the hospital did not decrease PTB in one trial in Zimbabwe (29).…”
Section: Bed Restmentioning
confidence: 91%